Impact of COVID-19 pandemic on the prevalence of respiratory viruses in children with lower respiratory tract infections in China - Liu, Pengcheng; Xu, Menghua; Cao, Lingfeng; Su, Liyun; Lu, Lijuan; Dong, Niuniu; Jia, Ran; Zhu, Xunhua; Xu, Jin (Virology journal, 2021)
The multifaceted non-pharmaceutical interventions (NPIs) taken during the COVID-19 pandemic not only decrease the spreading of the SARS-CoV-2, but have impact on the prevalence of other viruses. This study aimed to explore the prevalence of common respiratory viruses among hospitalized children with lower respiratory tract infections (LRTI) in China during the COVID-19 pandemic. Respiratory specimens were obtained from children with LRTI at Children's Hospital of Fudan University for detection of respiratory syncytial virus (RSV), adenovirus (ADV), parainfluenza virus (PIV) 1 to 3, influenza virus A (FluA), influenza virus B (FluB), human metapneumovirus (MPV) and rhinovirus (RV). The data were analyzed and compared between the year of 2020 (COVID-19 pandemic) and 2019 (before COVID-19 pandemic). A total of 7107 patients were enrolled, including 4600 patients in 2019 and 2507 patients in 2020. Compared with 2019, we observed an unprecedented reduction of RSV, ADV, FluA, FluB, and MPV infections in 2020, despite of reopening of schools in June, 2020. However, the RV infection was significantly increased in 2020 and a sharp increase was observed especially after reopening of schools. Besides, the PIV infection showed resurgent characteristic after September of 2020. The mixed infections were significantly less frequent in 2020 compared with the year of 2019. The NPIs during the COVID-19 pandemic have great impact on the prevalence of common respiratory viruses in China. Meanwhile, we do need to be cautious of a possible resurgence of some respiratory viruses as the COVID-19 restrictions are relaxed.